2005
DOI: 10.1007/s00436-005-0060-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of trypanocidal activity in plants used in Argentine traditional medicine

Abstract: Thirty-two organic and aqueous extracts, belonging to 12 Argentine medicinal plants were tested for their in vitro trypanocidal activity on epimastigote forms of Trypanosoma cruzi. Among the selected species, the organic extracts of Ambrosia scabra, Ambrosia tenuifolia, Baccharis spicata, Eupatorium buniifolium, Lippia integrifolia, Mulinum spinosum and Satureja parvifolia, and the aqueous extracts of E. buniifolium, L. integrifolia, M. spinosum and S. parvifolia showed trypanocidal activity with a percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 21 publications
1
24
0
1
Order By: Relevance
“…Our findings corroborate previously reported data on trypanocidal activity of Lippia species polar extracts (Abe et al 2005;Sülsen et al 2006). Sülsen et al (2006) reported in vitro activity of an organic and an aqueous extracts obtained from leaves of Lippia integrifolia against epimastigote forms of T. cruzi, with 34.5 and 71.2% inhibition, respectively, at 10 µg mL -1 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings corroborate previously reported data on trypanocidal activity of Lippia species polar extracts (Abe et al 2005;Sülsen et al 2006). Sülsen et al (2006) reported in vitro activity of an organic and an aqueous extracts obtained from leaves of Lippia integrifolia against epimastigote forms of T. cruzi, with 34.5 and 71.2% inhibition, respectively, at 10 µg mL -1 .…”
Section: Discussionsupporting
confidence: 93%
“…Sülsen et al (2006) reported in vitro activity of an organic and an aqueous extracts obtained from leaves of Lippia integrifolia against epimastigote forms of T. cruzi, with 34.5 and 71.2% inhibition, respectively, at 10 µg mL -1 . On the other hand, Abe et al (2005) reported in vitro activity of a methanol extract of Lippia dulcis leaves against trypomastigote forms of T. cruzi, with MIC (minimum inhibitory concentration) between 125 and 250 µg mL -1 .…”
Section: Discussionmentioning
confidence: 99%
“…The leishmanicidal and trypanocidal activity of essential oils from Lippia spp have been already demonstrated in some studies (Sulsen et al, 2006;Escobar et al, 2010 …”
Section: Discussionmentioning
confidence: 92%
“…Antioxidant, trypanocidal and antibacterial activities for this species have also been reported. [7][8][9] …”
Section: Introductionmentioning
confidence: 99%